Research priorities for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS): the results of a James Lind alliance priority setting exercise. Issue 4 (2nd October 2022) - Tyson, Sarah; Stanley, Kristina; Gronlund, Toto Anne; Leary, Sian; Emmans Dean, Mike; Dransfield, Claire; Baxter, Helen; Elliot, Rachel; Ephgrave, Rachel; Bolton, Monica; Barclay, Annette; Hoyes, Gemma; et al.
ABSTRACT: Objective: To identify research priorities of people with myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS) and those who support and care for them. Method: Using the James Lind Alliance's protocols, online surveys and workshops were held. The first survey asked participants from the U.K. to submit research questions about ME/CFS which were important to them. In the second, participants prioritised frequently submitted questions from the 1st survey. These were short listed and then workshop discussions were held to reach consensus on the top ten research priorities. Results: 1565 participated in the 1st survey and 5300 research priorities were submitted. 1752 participated in the 2nd. In both surveys, the predominant demographic was white, middle-aged women with ME/CFS. 15–17% were family/carers of people with ME/CFS and 4–6% were health and social care workers. From the 1st survey, 59 summary questions were identified. These were prioritised and short listed to 18 questions. Of these, the top 10 covered 1. Post-exertional malaise, 2. Use of existing drugs for other conditions, 3. Diagnosis, 4. Autoimmunity, 5. Sub-types, 6. Post-infective cause, 7. Neurological symptomology, 8. Genetics, 9. Severe ME/CFS, 10. Mitochronical dysfunction and 10 (equal) Oxygenation dysfunction. Conclusion: People with ME/CFS, their families and carers, and health care professionals worked together to identify, for the first time, the research priorities for ME/CFS. These focus on the biomedical causes of ME/CFS and how to diagnose, treat and manage it. Researchers and funding bodies should consider these in their plans for future research.